Biotechnological Micronutrient Production: Recombinant DNA Technology-Based Vitamin A Synthesis - Asli Giray; Sibel Pekdemir (Turkish Journal of Agriculture: Food Science and Technology)
Vitamin A is an essential micronutrient and has important functions such as vision, growth, reproduction embryogenesis, cellular differentiation, and proliferation, immune function and epithelial protector in the organism. Biotechnological production of vitamins is increasing due to their advantages and significant advances. The vitreoscilla hemoglobin (VHb) gene is extremely effective in binding oxygen and conducting it under hypoxic conditions. In this study, the production of vitamin A in E. herbicola (wild type) and its recombinant strains was investigated in LB medium and M9 medium (containing high concentrations (1%) of different carbon sources). The maximum production of vitamin A of the recombinant strain with the hemoglobin gene (vgb+) was observed in including glucose and sucrose M9 medium and their total product levels in vgb+ recombinant strain were 0.14 µg/ml and 0.1 µg/ml, respectively. The vitamin A production in the M9 medium with glucose and sucrose were 2-fold and 1.4- fold higher than that of the wild strain, respectively. The extracellular product level (0.07 µg/ml) in LB was 7-fold higher than wild strain at 48 h. These results reveal that the expression of VHb in E. herbicola in the both LB and M9 medium (containing 1% glucose and 1% sucrose, specially) increase the vitamin A production.